Adsorption of Some Heavy Elements on Surface of Activated Carbonized Cellulose from Aqueous Solution - Yaqoob , Ghassan Burhan (Journal of Petroleum Research and Studies, 2022)
In this study the activated carbonized cellulose in (350 ºC) by citric acid have been used to remove some heavy metals (Hg Cd, Cu, Pb) from its aqueous solution at room temperature. The adsorbed metals data applied on three adsorption isotherm models, Freundlich, Langmuir and Temkin isotherms. The adsorption results were very good fitted with isotherm models by the (R2) meaningful value. The removal metals adsorbed on surface of adsorbent from high to the less remove arranged according to its ability depending on the nature and size of metals. The free energy (ΔG) and constants of the adsorption process (Ɵ, n, kf, kT, b, bT) for copper, lead and cadmium were measured from isotherm curves, infra-red spectrums of the activated carbonized cellulose and cellulose itself were measured by FTIR spectrophotometer.